The Effect of Workload on the Performance of Nurses at Muslimat Ponorogo Hospital: Work Engagement and Job Satisfaction as Intervening Variables - Veprilia Permata Dewi; Majang Palupi (CV. Lenggogeni Data Publishing, 2024)
Abstract This research was purposed to analyze the relation between workload and nurse performance at Muslimat Hospital Ponorogo with work engagement and job satisfaction as intermediary variables. The method used in the research is quantitative with two-stage multiple linear regression as a measuring tool. The number of samples used in the research was 50 nurses at the Muslimat Hospital Ponorogo with various criteria of gender, age, length of work and different educational backgrounds. The research results show that workload directly has a positive and significant effect on performance, workload directly has a positive and significant effect on work engagement, while workload directly has no significant effect on nurse satisfaction. The relationship between work engagement and performance directly and job satisfaction has a significant effect. Meanwhile, work engagement and job satisfaction are considered not to be able to significantly mediate workload on nurse performance.